2005
DOI: 10.1093/pcp/pci150
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Regulates Fiber Development on Cultured Cotton Ovules

Abstract: Our current understanding of the role of phytohormones in the development of cotton fibers is derived largely from an amenable culture system in which cotton ovules, collected on the day of anthesis, are floated on liquid media. Under these conditions, supplemental auxin and gibberellin were found to promote fiber initiation and elongation. More recently, addition of low concentrations of the brassinosteroid brassinolide (BL) were also found to promote fiber elongation while a brassinosteroid biosynthesis inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 30 publications
2
124
0
1
Order By: Relevance
“…Diverse signal transduction pathways were found to be involved in the regulation of fiber elongation including ethylene-, brassinosteroid (BR)-and auxin-mediated signalings. 5,8,45,46 We have previously reported that calcium signaling components such as calmodulin, CBL (calcineurin B-like protein) and CDPK (Ca 2+ -dependent protein kinase) are up-regulated during fiber elongation. 47,48 Here we found that the expression of a calmodulin was highly suppressed in Li 1 fiber, thus further demonstrating the role of calcium signaling in fiber elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse signal transduction pathways were found to be involved in the regulation of fiber elongation including ethylene-, brassinosteroid (BR)-and auxin-mediated signalings. 5,8,45,46 We have previously reported that calcium signaling components such as calmodulin, CBL (calcineurin B-like protein) and CDPK (Ca 2+ -dependent protein kinase) are up-regulated during fiber elongation. 47,48 Here we found that the expression of a calmodulin was highly suppressed in Li 1 fiber, thus further demonstrating the role of calcium signaling in fiber elongation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, based on the signalling pattern, Br signalling in plants has been correlated with metazoan Wnt like signalling. It is reported that Br is involved in the process of callusing, somatic embryogenesis 82 and promotes fibre initiation and elongation in Gossypium 83,84 . This role of Br is rather comparable to that of Wnt's action in animals where Wnt promotes embryogenesis and cell reprogramming.…”
Section: Wnt Signalling In Gossypium!!mentioning
confidence: 99%
“…Fiber length was measured using the water washing method [26]. The ovules were boiled in water for 2 min to detach fibers, and after cooling, the ovules were placed on a slide and rinsed with purified water.…”
Section: Determination Of Fiber and Ovule Growth Parametersmentioning
confidence: 99%